Kompetensi Profesional dan Kreativitas Guru dalam Pembelajaran Berkualitas - Darmawan, Didit; Qomariyah, Galuh Fitri Ayu Nur (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the development of teachers’ professional competence and creativity, as well as their contribution to improving the quality of learning. The study employs a qualitative literature review method using content analysis techniques applied to relevant scientific articles, books, and academic publications. The data were analysed by identifying key themes relating to teachers’ professional competence, creativity in teaching, and their implications for the quality of the teaching and learning process. The results of the analysis indicate that teachers’ professional competence plays a crucial role through mastery of subject matter, understanding of learners’ characteristics, the ability to design and deliver learning, classroom management, the use of technology, and the evaluation and reflection on learning. Meanwhile, teachers’ creativity contributes through the ability to deliver innovative, flexible, and contextual learning that fosters student engagement and motivation. These two dimensions complement one another and together form effective, meaningful, and enjoyable learning. These findings suggest that teachers’ professional development should not only focus on technical aspects but also on strengthening pedagogical creativity. Further research is recommended to test the relationship between these two variables through an empirical approach